Multiobjective electric vehicle charging station locations in a city scale area: Malaga study case. - Cintrano López, Christian; Toutouh-el-Alamin, Jamal (My University, 2022)
This article presents a multiobjective variation of the problem of locating electric vehicle charging stations (EVCS) in a city known as the Multiobjective Electric Vehicle Charging Stations Locations (MO-EVCS-L) problem. MO-EVCS-L considers two conflicting objectives: maximizing the quality of service of the charging station network and minimizing the deployment cost when installing different types of charging stations. Two multiobjective metaheuristics are proposed to address MO-EVCS-L: the Non-dominated Sorting Genetic Algorithm, version II (NSGA-II) and the Strength Pareto Evolutionary Algorithm, version 2 (SPEA2). The experimental analysis is performed on a real-world case study defined in Malaga, Spain, and it compares the proposed approaches with a baseline algorithm. Results show that the SPEA2 computes the most competitive solutions, even though both metaheuristics found an accurate set of solutions that provide different trade-offs between the quality of service and the installation costs.
Keywords: Transporte - Aspectos ambientales; Desarrollo sostenible; Vehículos eléctricos; Electric vehicles; Infrastructure location; Sustainable mobility; Multiobjective optimization; NSGA-II; SPEA2